The JWST rocky worlds DDT program reveals GJ 3929b to likely be a bare rock - Xue, Qiao; Zhang, Michael; Coy, Brandon Park; Brady, Madison; Ji, Xuan; Bean, Jacob L.; Radica, Michael; Seifahrt, Andreas; Stürmer, Julian; Luque, Rafael; Basant, Ritvik; Brown, Nina; et al. (The astrophysical journal. Part 2, Letters, 2025)
We report first results from the JWST Rocky Worlds Director’s Discretionary Time program. Two secondary eclipses of the terrestrial exoplanet GJ 3929b were recently observed using MIRI photometric imaging at 15 μm. We present a reduction of these data using the updated SPARTA pipeline. We also refine the planet mass, radius, and predicted time of secondary eclipse using a new sector of TESS data and new, high-precision radial velocities from the MAROON-X spectrograph. For the two JWST observations, we recover secondary eclipse depths of 177 ppm and 143 ppm at times consistent with a nearly circular orbit, as expected from the radial velocity data. A joint fit of the two visits yields a dayside brightness temperature Tp,dayside = 782 ± 79 K for GJ 3929b, which is consistent with the maximum brightness temperature K for a bare black rock (i.e., assuming zero Bond albedo and no heat redistribution). These results rule out CO2-rich atmospheres thicker than 100 mbar at >3σ, suggesting that GJ 3929b has lost any significant secondary atmosphere. The radial velocity data also indicate two additional nontransiting planets in the system: a previously identified planet in a 15.0 days orbit and a newly identified planet candidate in a 6.1 days orbit.
Veröffentlicht: 12. Dezember 2025
Gesehen am 11.02.2026